Inovasi Produk Berbasis Limbah Kulit Singkong dalam Mendorong Usaha Kreatif Masyarakat Desa Sumberpitu - Riska Andi Fitriono; Rizqon Farisi; Meiliana Hapsari; Nabilah Nurulhumairoh; Miftahul Jannah; Yeni Fatmawati; Zinorio De Jesus; Artita Masfifatul Afif; Nindya Nourma Shanti; Siti Dian Adriani; Yoga Prasetya Ramadhana (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Cassava waste is commonly used as animal feed or simply discarded by the community of Sumberpitu Village, Cepu Subdistrict, Blora Regency. Waste that is discarded without being processed can pollute the environment and cause disease. Therefore, the aim of this community service activity is to provide training on processing cassava peels into delicious and safe food, encouraging the community to start entrepreneurial ventures to improve the local economy. This activity includes a brief explanation of cassava peel waste processing, followed by a demonstration of making cassava peel chips. The method used in this activity consists of three stages: identifying the problem, program planning, and program implementation. This initiative is expected to reduce cassava peel waste in Sumberpitu Village and increase community income through creative and innovative waste processing.